HTS Josephson junctions arrays for high-frequency mixing. (24th January 2018) - Sharafiev, A; Malnou, M; Feuillet-Palma, C; Ulysse, C; Wolf, T; Couëdo, F; Febvre, P; Lesueur, J; Bergeal, N
Abstract: We designed, fabricated and measured short one-dimensional arrays of masked ion-irradiated YBa 2 Cu 3 O 7 Josephson junctions embedded into log-periodic spiral antennas. They consist of four or eight junctions separated either by 960 nm or 80 nm long areas of pristine material. Large spacing arrays show 'giant' Shapiro steps in the hundreds-GHz band at 66 K and are tested as Josephson mixers with improved impedance matching. On the contrary, small spacing arrays behave as one junction with a lower superconducting transition temperature, hence forming a single weak link on distances up to 880 nm. Such design opens a new way to increase the I c R n product of the devices, and therefore the efficiency of Josephson mixers. Hints on the origin of the observed long range proximity effect are proposed.